2018
DOI: 10.3389/fmicb.2018.02260
|View full text |Cite
|
Sign up to set email alerts
|

FtsZ of Filamentous, Heterocyst-Forming Cyanobacteria Has a Conserved N-Terminal Peptide Required for Normal FtsZ Polymerization and Cell Division

Abstract: Filamentous cyanobacteria grow by intercalary cell division, which should involve distinct steps compared to those producing separate daughter cells. The N-terminal region of FtsZ is highly conserved in the clade of filamentous cyanobacteria capable of cell differentiation. A derivative of the model strain Anabaena sp. PCC 7120 expressing only an FtsZ lacking the amino acids 2–51 of the N-terminal peptide (ΔN-FtsZ) could not be segregated. Strain CSL110 expresses both ΔN-FtsZ, from the endogenous ftsZ gene pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 72 publications
(107 reference statements)
2
37
0
Order By: Relevance
“…We have also studied the localization of FtsZ upon N-stepdown in Anabaena strain CSSC19, which expresses a ftsZ-gfp-mut2 gene fusion placed at the ftsZ locus and which keeps an intact copy of ftsZ also expressed from the native promoter ( 19 ) ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also studied the localization of FtsZ upon N-stepdown in Anabaena strain CSSC19, which expresses a ftsZ-gfp-mut2 gene fusion placed at the ftsZ locus and which keeps an intact copy of ftsZ also expressed from the native promoter ( 19 ) ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Localization of FtsZ during heterocyst differentiation in Anabaena. (A) Schematic of the genome structure of strain CSSC19 (ftsZ-gfp-mut2)(19) in comparison to PCC 7120 (WT). The gray trace represents an inserted plasmid encoding resistance to Sm and Sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates that the FtsZ circles might be useful for its function. Recently, Corrales-Guerrero L et al (41) reported that deletion of N-terminus of Anabaena FtsZ, another cyanobacterial FtsZ, only formed straight bundles. These mutant FtsZs might cause the aberrant Z-structures and asymmetric cell division.…”
Section: Discussionmentioning
confidence: 99%
“…These mutant FtsZs might cause the aberrant Z-structures and asymmetric cell division. It indicated that the formation of the medium circles might be necessary for its function, and even it cannot be excluded the possibility that deletion might affect the binding with the other association proteins (41).…”
Section: Discussionmentioning
confidence: 99%